A política energética russa no governo putin-medvedev (2000-2018) - Albuquerque, Fernanda Patrícia Silva (2019)
After the collapse of the Soviet Union, in 1991, the government of Boris Yeltsin (1991-1999) moved, at the same time, to a democratic political regime and a liberal capitalist economy. These transformations provoked political instability and an economic crisis that lasted throughout the 1990s. In 2000, Vladimir Putin assumed the presidency with the mission to recover the economy and reinsert the country as a power in the international scenario. Putin considers the energy industry the strategic sector of the Russian economy, because of the abundance of natural resources and the presence of an already well-developed energy infrastructure. So, Putin implements an energy policy aimed at overcoming internal and external problems. Thus, this research has the central objective of investigating whether the energy policy, implemented by Vladimir Putin in the years 2000, was one of the elements that strengthened and contributed to the reintegration of Russia in the international scenario. With the purpose of deepening the previous objective, it is also dedicated to the case study in which China's relevance in Russia's energy policy is analyzed, because since after the Crisis of Ukraine (2014), which resulted in the annexation of Crimea by Russia and in sanctions imposed by Western powers, Moscow has intensified its redirection to Asia. This dissertation - of a qualitative, documentary and descriptive character - is divided into three chapters: the first, presents the domestic scenario and Russian foreign policy in the period 2000-2018; the second, examines energy policy; and the third, examines Sino-Russian energy cooperation. It is concluded that Putin's energy policy was successful, given the country's economic recovery, its major role in the international arena (as opposed to the 1990s), and the partnership built with China, which was essential to ensure capital and diversify Russian demand after the sanctions imposed in 2014.